Framing analysis of the hacking of Bank Syariah Indonesia by LockBit Ransomware on Republika.co.id and Idntimes.com - Nurjanah, Indah; Hariyanto, Didik (Universitas Ahmad Dahlan, 2024)
This research aims to analyze the framing of news by Republika.co.id and Idntimes.com regarding the phenomenon of hacking Bank Syariah Indonesia by LockBit 3.0 Ransomware. This research was conducted because the hacking issue of Bank Syariah Indonesia became the major topic of public interest and impacted the perceived security of data and funds. The sensitive issue of security hacking certainly has economic relevance for both the public and investors of Bank Syariah Indonesia. The contribution of this study is to provide a nuanced understanding of how different online media outlets frame the same cybersecurity incident, thereby offering insights into the role of media narratives in shaping public perceptions and trust in the banking sector in the digital era. The research method used is a qualitative approach with Robert N. Entman’s framing analysis model, which has four major elements to interpret the news: define problem, diagnose causes, make moral judgement, and treatment recommendation. The result showed that Republika.co.id sharply criticized Bank Syariah Indonesia in its reporting, but did not emphasize the ransom demand made by LockBit. The criticism in its reporting humanistically and in favor of the community. Meanwhile, Idntimes.com attempted to downplay the inevitability of cyberattacks in the IT world, and framed the news of Bank Syariah Indonesia hacking by LockBit by playing on public emotions using clickbait, rather than highlighting the mitigation steps taken by Bank Syariah Indonesia.